COMPARISON OF THE EFFECTIVENESS OF THERAPY IN HYDRODISSECTION INJECTION USING ULTRASONOGRAPHY GUIDENCE BETWEEN NORMAL SALINE AND TRIAMCINOLONE IN CARPAL TUNNEL SYNDROME PATIENTS - Santoso, Widodo Mardi; Rakhmatiar, Rodhiyan; Rakhmani, Alidha Nur; Sahidu, Muhammad Ghalvan (Malang Neurology Journal, 2020)
Background: Carpal tunnel syndrome (CTS) is a peripheral nerve lesion because of the nontraumatic mechanism or a pressure or entrapment of the median nerve under the transverse ligament (flexor retinaculum). Hydrodisection is used for adhesiolysis to eliminate adhesion and release the median nerve from the retinaculum and connective tissue around it and avoid injury to the nerves. Objective: Compare the effectiveness of hydrodisection injection therapy using an ultrasound guide between normal saline and triamcinolone in patients with carpal tunnel syndrome.Methods: Experimental study was carried out in the outpatient clinic of the hospital Dr. Saiful Anwar Malang from August 2018 to October 2018. A total of 30 patients. All study subjects were subjected to NPS, FSS, SSS scoring compared to before and 4 weeks after injection of hydrodisection and compared the effectiveness of injection agents.Results: NPS before and after triamcinolone injection (sig 0.000; p <0.05), FSS (sig 0.020; p <0.05), and SSS (sig 0.001; p <0.05). NPS before and after injection of normal saline 0.9% NaCl  (sig 0.001; p <0.05), FSS (sig 0.005; p <0.05), and SSS (sig 0,000; p <0.05). NPS between triamcinolone injection results and normal saline 0,9% NaCl  (sig 0.341; p <0.05), FSS (sig 0.425; p <0.05), SSS (sig 0.350; p <0.05).Conclusion: There no significant difference between injection of hydrodisection USG guiding with triamcinolone and normal saline 0,9% NaCl to reduce symptom CTS. Both of injection hydrodisection USG guiding has more or less the same effectiveness in treatment of carpal tunnel syndrome.Keywords: CTS, Hydrodisection, NPS, FSS, SSS